Measurement comparison among time-domain, FTIR and VNA-based spectrometers in the THz frequency range. (20th January 2017) - Oberto, L; Bisi, M; Kazemipour, A; Steiger, A; Kleine-Ostmann, T; Schrader, T
Abstract: In this paper we present the outcome of the first international comparison in the terahertz frequency range among three different kinds of spectrometers. A Fourier-Transform infrared spectrometer, a vector network analyzer and a time-domain spectrometer have been employed for measuring the complex refractive index of three travelling standards made of selected dielectric materials in order to offer a wide enough range of parameters to be measured. The three spectrometers have been compared in terms of measurement capability and uncertainty.